Chaperones: Methods and Protocols - Calderwood, Stuart K.; Prince, Thomas L. (Methods in molecular biology, 2018)
Targeted Deletion of Hsf1, 2 and 4 Genes in Mice -- Role of Heat Shock Factors in Stress-induced Transcription -- Monitoring of the Heat Shock Response with a Real-time Luciferase Reporter -- Quantitative Profiling of Chaperone/client Interactions with LUMIER Assay -- Measurement of chaperone-mediated effects on Polyglutamine Protein Aggregation by the Filter Trap Assay -- Fluorescent-linked Enzyme Chemoproteomic Strategy (FLECS) for Identifying HSP70 Inhibitors -- A High-throughput Screen for Inhibitors of the Hsp90-Chaperone Machine -- Primary Colorectal Cells Culture as a Translation Research Model -- Cell Death and Survival Assays -- Detecting the Potential Pharmacological Synergy of Drug Combination by Viability Assays In Vitro0pt;"> -- nt-size: 12.0ptProteomic Profiling of Hsp90 Inhibitors -- Analysis of HspB1 (Hsp27) Oligomerization and Phosphorylation Patterns and its Interaction with Specific Client Polypeptides -- Nucleotide Exchange Factors for Hsp70 Chaperones -- Determination of Hsp90 Activity through Activation of Glucocorticoid Receptors in Yeast -- Bacterial Hsp90 ATPase Assays -- Detecting Post-translational Modifications of Hsp90 -- Chromatin Immunoprecipitation (ChIP) of Heat Shock Protein 90 (Hsp90) -- background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; font-size: 12pt; font-family: "Times New Roman", serif; color: rgb(33, 33, 33);">A Workflow Guide to RNA-seq Analysis of Chaperone Function and Beyond -- Computational Modeling of the Hsp90 Interactions with Cochaperones and Small Molecule Inhibitors -- Computational Analysis of the Chaperone Interaction Networks -- Immunohistochemistry of Human Hsp60 in Health and Disease: From Autoimmunity to Cancer -- Immunohistochemical and Flow Cytometric Analysis of Intracellular and Membrane-bound Hsp70, as a Putative Biomarker of Glioblastoma Multiforme, using the cmHsp70.1 MonoclonalDetection and Analysis of Extracellular Hsp90 (eHsp90) -- Molecular Chaperone Receptors -- Creation of Recombinant Chaperone Vaccine using Large Heat Shock Protein for Antigen-targeted Cancer Immunotherapy -- A Novel Heat Shock Protein 70-based Vaccine Prepared from DC-Tumor Fusion Cells -- Hsp70: A Cancer Target Inside and Outside the Cell -- Evidence for Hsp90 Cochaperones in Regulating Hsp90 Function and Promoting Client Protein Folding -- Clinical Evaluation and Biomarker Profiling of Hsp90 Inhibitors.n>ttom:.0001pt;line-height: normal;mso-layout-grid-align:none;text-autospace:none">.
Keywords: Polypeptidketten bindende Proteine